A percepção do farmacêutico no processo de implantação de serviços clínicos farmacêuticos - Dosea, Aline Santana (2015)
In community pharmacies, at the time the pharmacist incorporates clinical practice into their routine, several barriers and facilitators influencing the implementation of patient care services. Objectives: To learn and understand the perception of a group of pharmacists on the process of implementation of Clinical Pharmacy Services in community pharmacies; Understand through a Scoping Review of literature, pharmacist perception about Clinical Pharmacy Services in community pharmacy. Methods: The study was structured in two stages. The first step corresponded to Scoping Review held in the Lilacs, PubMed, Scopus, Scielo and Web of Knowledge database. Studies should be of the pharmacist perception, and the pharmaceutical services should be patient-focused. The second stage corresponded to a qualitative study in which three focus groups were conducted with a group of 11 pharmacists. Data analysis was done using the technique of content analysis. Results: Step 1 - The literature search resulted in 29 articles that met the inclusion criteria. The studies were performed in eight different countries, had qualitative methods (focus groups, interviews, diaries and questionnaires) and quantitative (questionnaires) and 12 different classifications of pharmaceutical services were found. In most studies, pharmacists believed that their role in community pharmacies was positive for patients, barriers and facilitators for service were reported. Step 2 - The audio recording of the focus groups were fully transcribed and analyzed. The perception of pharmacists brought issues such as access to medication, barriers and facilitators to service, expectations, changes generated during the implementation of services, results achieved and consolidation of services. Conclusion: The Scoping Review made recommendations for implementation of Clinical Services Pharmacists in community pharmacies, making it easier to service delivery and enhancing practices in community pharmacies. The dissemination of positive experiences in implementations of services through perception studies have shown that it is possible to develop a model of clinical services in community pharmacies.